Physico-Chemical And Energy Properties Of Biomass Briquettes Composed From Dairy Cow Feces And Coffee Ground With Tapioca Flour Addition - Rahmaisyanti, Alya; Sofyan, Ahmad; Sulistyati, Marina; Hidayati, Yuli Astuti (Fakultas Peternakan, Universitas Padjadjaran, 2024)
Cow feces is the rest of the digestive process of the livestock body, while coffee grounds are the rest of coffee brewing, and both are organic materials with fixed carbon that can be utilized as fuel. The purpose of this study was to determine the effect of the addition of coffee grounds in processing dairy cow feces into briquettes on physical properties (color, texture, density), chemical properties (moisture content, ash content, volatile matter, and fixed carbon), and energy value (calorific value, temperature, flame duration). This research method is experimental, with four treatments, each consisting of five repetitions. The treatments in this study consisted of P1 (100 g dairy cow feces + 20 g coffee grounds), P2 (100 g dairy cow feces + 40 g coffee grounds), P3 (100 g dairy cow feces + 60 g coffee grounds), P4 (100 g dairy cow feces + 80 g coffee grounds). The data obtained were analyzed statistically with ANOVA at = 5%. Further tests were carried out using the Duncan test. The results showed that the addition of coffee grounds to dairy cow feces briquettes had a significant effect (p<0.05) on physical properties (density), chemical properties (moisture content, ash content, volatile substances, fixed carbon) and energy value (calorific value, temperature, and flame duration). The addition of 80 grams of coffee grounds (P4) gave the best effect on the performance of dairy cow feces briquettes with a moisture content of 6.94%, ash content of 25.47%, volatile matter of 18.58%, fixed carbon of 49.02%, calorific value of 3717 cal/gr, temperature of 463°C.